(untitled) (Riwayat: Educational Journal of History and Humanities, 2026)
The rapid growth of e-commerce in Indonesia has intensified competition between platforms, especially between e-commerce platforms. Meanwhile, Tokopedia’s index in the Top Brand Award has shown a downward trend over the past five years, but user preference for this platform remains very high. This study examines how website design and information quality influence customer loyalty, both directly and through customer e-satisfaction, among Tokopedia users in Semarang City. This research uses an explanatory quantitative approach with a population of active Tokopedia users in Semarang City. The sample consisted of 199 respondents. Sampling was conducted using purposive sampling techniques, and data was collected through an online questionnaire. The data was analyzed using (SEM-PLS). The results showed that customer loyalty was influenced by information quality and customer e-satisfaction, while website design was found to have no direct influence on loyalty. Website design and information quality were also found to have a significant influence on the customer e-satisfaction variable. Furthermore, customer e-satisfaction significantly mediates the relationship between website design and customer loyalty, as well as mediates the relationship between information quality and customer loyalty. These findings highlight the central role of information quality and customer satisfaction in strengthening loyalty, and suggest that Tokopedia should prioritize improving information quality and user experience design to increase long-term customer retention.